Semangat Kerja Guru berdasarkan Lingkungan Kerja di SD XXX - Silvia Nursafitri; Achmad Fauzi; Dian Sudiantini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research was conducted to determine teacher work morale based on the work environment at SD XXX. The research focus in this study is Teacher Work Morale and Work Environment, according to the explanation that has been given, a problem formulation can be made, namely from this research is Teacher Work Morale based on Work Environment at SD XXX. This research is qualitative research with data collection techniques, namely field observations, interviews with informants, and documentation. In the research findings from interviews with informants, namely in the observation notes in the sub-focus section, the availability of work facilities, work systems and discipline at work are still weaknesses in the observations.